Simultaneous Detection of Anions and Carbohydrates in Cyanobacteria by Two-Dimensional Ion Chromatography. (17th November 2020) - Jiang, Lijun; Bao, Yan; Guo, Liang; Cui, He; Wang, Qi; Liu, Kai; Hao, Xiaoxian; Qiu, Ruchen; Guo, Zhiyan; Fa, Yun
Abstract: Background: The simultaneous analysis of several anions and carbohydrates by one-dimensional chromatography with a single detector is often complicated by the presence of overlapping peaks. To overcome this problem, analytes are usually analyzed separately making analysis long and tedious. Objective: A method combining two-dimensional ion chromatography (2D-IC) and valve switching was developed for the simultaneous determination of anions (F −, Cl −, NO 2 −, SO 4 2 −, NO 3 −, and PO 4 3 − ) and carbohydrates (glycerin, glucosyl glycerol, trehalose, mannose, glucose, galactose, fructose, ribose, and sucrose) in cyanobacteria. Method: Interfering color compounds were removed by first passing the sample through graphitized carbon solid phase extraction (SPE) cartridges. Samples were applied to an AS11-HC column, which was used to separate the anions followed by quantification using a conductance detector. Carbohydrates eluted from the AS11-HC column were trapped and separated on a MA1 column and simultaneously quantified using electrochemical detection in the second dimension with valve switching. Results: The following parameters were established: LOD, 0.001–0.030 (mg/L); LOQ, 0.001–0.010 (mg/L); linearity ( R 2 ), 0.9940; repeatability, 0.39–3.02%; and spiked recovery, 90.1–107%. Conclusions: The proposed method is adequately linear, accurate, and repeatable. The 2D-IC method provides fast, high-resolution, and completely automated procedure for the simultaneous determination of anions and carbohydrates without co-elution compared to the 1D ion chromatography method. This study provides application perspectives for use in biotechnology and other research fields. Highlights: An accurate and effective 2D-IC method was developed for determining anions and carbohydrates in cyanobacteria. The method includes pre-treating samples with graphitized carbon SPE cartridges.